Pontic and Transcarpathian Cultural Patterns in the Trzciniec Circle Between the Prosna and Dnieper - Makarowicz, Przemysław; Górski, Jacek; Lysenko, Sergey D. (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2013)
In 2009, the 14th volume of Baltic-Pontic Studies (BPS) ran a series of papers summing up the state of research at that time into the routes between the Baltic and Black seas between the 4th and 1st mill. BC. They are an expression of an early reflection prompted by the need to look more closely at the impact Pontic cultural environments – where composite metallurgy was practised, designated as Early Bronze in this volume – had on the Decline Neolithic and Proto-Bronze settlement centres in the Baltic drainage basin. It is to this question that successive volumes of the BPS shall be devoted. Specifically, according to the research programme aims mentioned above (initial fruits being the papers included in BPS, vol. 18) the environments of Northern Pontic cultures – Yamnaya, Catacomb and Babyno – and the Trzciniec cultural circle were identified as generators of the Ingul-Donets Early Bronze Civilization or their immediate neighbours. In proposing this modification of the gamut of phenomena making up the prologue to the European Bronze Age, we intend to suggest the need for a more integrated (‘extra-taxonomic’) and at the same time, territorially wide-ranging reading of Northern Pontic civilization environments and its cultural interaction in the period from the 3rd to the first half of the 2nd mill. BC. More arguments in favour of the above opinion can be found in the introductory paper: The Baltic Drainage Basin in the Reconstruction of the Mental Map of Central Europe Held in Common by Northern-Pontic Early-Bronze Civilization Communities; 3200 – 1600 BC, An outline of research programme.